2022
DOI: 10.5817/cp2022-3-7
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between passion for playing video games and behavioral school engagement: Mediation through time spent playing

Abstract: The aim of this study was to examine the relationship of harmonious and obsessive passion for playing video games with behavioral school engagement, and to determine whether these two types of passion are indirectly related to behavioral school engagement through time spent playing video games. Data for this correlational, on-line study were collected from a convenience quota sample of 568 high-school students (55.5% boys) between 14 and 19 years old (M = 15.89; SD = 1.16). Participants self-reported their pas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 37 publications
0
3
0
1
Order By: Relevance
“…Lotar Rihtarić et al (2022) relacionaron significativamente (p<0,05) al tiempo de dedicación a los videojuegos con el compromiso académico de los adolescentes estudiados, resultando inversamente proporcional y con intensidad débil (r=-0,12).…”
Section: Discussionunclassified
“…Lotar Rihtarić et al (2022) relacionaron significativamente (p<0,05) al tiempo de dedicación a los videojuegos con el compromiso académico de los adolescentes estudiados, resultando inversamente proporcional y con intensidad débil (r=-0,12).…”
Section: Discussionunclassified
“…Examination of previous studies and research related to the emotion of learning and its effects on the organization and management of knowledge in distance learning environments [5,[32][33][34]36,38,48].…”
Section: Study Toolsmentioning
confidence: 99%
“…Additionally, the study indicated that self-regulation played a more comprehensive role in explaining the interplay between emotion and well-being [ 32 ]. Similarly, Rihtarić, et al [ 33 ] conducted a study to investigate the connection between harmonious and obsessive cravings for video games, school behavioral interaction, and their indirect relationship with school engagement through gaming time. Utilizing the binary emotion model, their pathway analysis unveiled direct effects of both harmonious and obsessive cravings on school behavioral reactivity, along with indirect effects through time spent playing video games.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation